2014
DOI: 10.1111/ejn.12519
|View full text |Cite
|
Sign up to set email alerts
|

Auxiliary proteins promote modal gating of AMPA‐ and kainate‐type glutamate receptors

Abstract: The gating behavior of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and kainate receptors is modulated by association with the auxiliary proteins: transmembrane AMPA receptor regulatory proteins (TARPs) and neuropilin tolloid-like (Netos), respectively. Although the mechanisms underlying receptor modulation differ for both AMPA and kainate receptors, association with these auxiliary subunits results in the appearance of a slow component in the decay of ensemble responses to rapid applications of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
92
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(103 citation statements)
references
References 63 publications
11
92
0
Order By: Relevance
“…A saturating concentration of JNJ-55511118 reduces peak responses by 36-44%, and steadystate currents by ∼75%. This reduction is consistent with masking the increases in single-channel conductance observed in studies of single-channel kinetics of TARPed versus TARP-less AMPA receptors (Shelley et al, 2012;Zhang et al, 2014). This inhibition is accompanied by an increase in the desensitization and deactivation kinetic rates.…”
Section: Discussionsupporting
confidence: 82%
“…A saturating concentration of JNJ-55511118 reduces peak responses by 36-44%, and steadystate currents by ∼75%. This reduction is consistent with masking the increases in single-channel conductance observed in studies of single-channel kinetics of TARPed versus TARP-less AMPA receptors (Shelley et al, 2012;Zhang et al, 2014). This inhibition is accompanied by an increase in the desensitization and deactivation kinetic rates.…”
Section: Discussionsupporting
confidence: 82%
“…1C; fig. S2), as expected (2630). Thus, the presence of the GT linker between GluA2 and STZ in our GluA2-STZ construct did not significantly affect modulation of GluA2 function by STZ.…”
supporting
confidence: 85%
“…Single-channel studies have shown that AMPARs open to various distinct subconductance states (Wyllie et al, 1993;Swanson et al, 1997) thought to reflect the number of subunits individually activated (Rosenmund et al, 1998;Smith and Howe, 2000;Gebhardt and Cull-Candy, 2006). Thus, an increased mean conductance could reflect an increase in the proportion of openings to the larger subconductance states-altered gating-or an increase in the conductance of all states (altered permeation; Tomita et al, 2005;Shelley et al, 2012;Zhang et al, 2014). Our present data do not allow us to distinguish between these two possibilities.…”
Section: Role Of the C-tail Of ␥-2 In Ampar Functionmentioning
confidence: 56%